Enhancing the Digital Competencies of MSME Actors Fostered by Rumah BUMN Yogyakarta - Mugi Puspita; Irfan Achmad Musadat; Agung Pramayuda (International Journal Of Community Service, 2026)
This community service (PKM) program aimed to enhance the digital competencies of micro, small, and medium-sized enterprises (MSMEs) fostered by Rumah BUMN Yogyakarta in response to rapid technological developments and increasing demands for digital transformation. Limited understanding of digital marketing, the use of e-commerce platforms, and social media management has been a major barrier preventing MSMEs from expanding their market reach and improving competitiveness. Through a training and mentoring program covering basic digital literacy, social media optimization, marketplace introduction, and digital content creation techniques, participants were equipped with practical skills that could be directly applied to their businesses. The program employed an implementation method based on interactive discussions between business actors and resource persons. Evaluation results indicated improvements in participants’ knowledge and skills in leveraging digital technologies for promotion and business management. In addition, participants were able to develop more effective digital marketing strategies tailored to the characteristics of their respective products. This program is expected to strengthen MSMEs’ capacity to adapt to the digital business ecosystem and to support local economic growth in Yogyakarta.